PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PENGGUNAAN LEARNING MANAGEMENT SYSTEM (LMS) PADA KARYAWAN PT WAHANA INTI SELARAS - Yemin Setiawan (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2022)
The problem in this research is in employee training at the Company, at this time the world and Indonesia conditions are experiencing the COVID-19 pandemic so that in accordance with the government's call for working from home and social distancing, it is necessary to adjust the design of the training carried out with information technology assistance, namely through the Learning Management System (LMS). This study aims to analyze the satisfaction of LMS users which is influenced by the quality of the system, the quality of information, and the quality of service to the employees of PT Wahana Inti Selaras. The study used a random sampling technique by distributing online questionnaires to the employees of PT Wahana Inti Selaras through google forms. The research data was processed quantitatively descriptively with path analysis techniques, using IBM SPSS version 23. The research results were supported by primary data obtained from the results of filling out questionnaires. The results showed that: (1) the quality of the system has a positive and significant effect on the satisfaction of using the LMS. (2) The quality of information has a positive and significant effect on the satisfaction of using the LMS. (3) Service quality has a positive and significant effect on the satisfaction of using LMS.